Precautionary Measures: Performing ERCP on a Patient With Juxtapapillary Duodenal Diverticula (JPDD)-Related Biliary Stone After COVID-19 Lockdown Restriction Lifted in Wuhan, China - Chen, Qian; Yang, Min; Liao, Guang-quan; Zhao, Yu-er; Yue, Dao-yuan; Yuan, Yue; Cheng, Bin; Qin, Hua (Frontiers in Medicine, 2020)
On April 8, 2020, after nearly three months of our battle against COVID-19 outbreak, Wuhan where the pandemic began has eased the lockdown restriction. However, given that those asymptomatic carriers could lead to transmission of COVID-19 during very early stage, the endoscopists take precautions and conduct risk assessment to perform endoscopic intervention in this transition stage. Here, we reported an urgent ERCP in a patient with acute pancreatitis secondary to JPDD-related biliary stone. Based on our experiences, the objective is to provide practical suggestions for safely resume the ERCP procedures in the setting of COVID-19 pandemic, with specific focus on patient risk assessment, personal protection equipment (PPE) and dressing code modalities, all of which have been implemented in our hospital to reduce the risk of viral transmission.